The first step is to multiply the #1/2# term through the #(x-6)# term.

#1/2x-1/2(6)+1/4(x-12) = 2 - x#

Because one half of six is three, we can rewrite it as

#1/2x-3+1/4(x-12)=2-x#

Next, multiply the #1/4# term through the #(x-12)# term.

#1/2x - 3 + 1/4x-1/4(12)=2-x#

Because one quarter of 12 is 3, we can rewrite it as

#1/2x - 3 + 1/4x-3=2-x#

You can combine the #1/2x# and the #1/4x#. Because

#1/2+1/4=2/4 + 1/4=3/4#, we can rewrite our equation as

#3/4x - 3 -3=2-x#

Because negative 3 minus 3 is negative six, we can rewrite

#3/4x-6=2-x#

Add #6# to both sides

#3/4x=8-x#

Add #x# to both sides

#3/4x+x=8#

Because #x# is really just #1xxx#, we can rewrite as

#3/4x+1xxx=8#

#3/4x+4/4x=8#

#7/4x=8#

Multiply both sides by #4#

#7x=32#

Divide both sides by 7

#x=32/7#